Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1111/j.1365-2621.2004.tb10699.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Moisture and Water Activity of Honeys Harvested in Different Years

Abstract: For the 1st time, a relationship has been investigated between moisture percentage (M) and water activity (aW) in honeys from 2 different harvesting years and 2 different climatic areas. Moisture was determined by measuring refractive index at 20°C, according to official methods. At the same time, aW of the same samples was assessed at exactly 20°C. Influence on the relationship of the crop's year, aging, and induced fine granulation was evaluated. The results show that, independent of all factors studied, an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
20
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 7 publications
8
20
0
Order By: Relevance
“…In flower honeys the water activity was in the range from 0.479 to 0.557, the mean value was 0.521. These values agree with previously reported data for water activity (Cavia et al, 2004;Gleiter, Horn, & Isengard, 2006;. Since osmophilic yeasts are only able to grow above minimal water activity of 0.6, the honeys under investigation should be regarded as safe with respect to fermentation.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…In flower honeys the water activity was in the range from 0.479 to 0.557, the mean value was 0.521. These values agree with previously reported data for water activity (Cavia et al, 2004;Gleiter, Horn, & Isengard, 2006;. Since osmophilic yeasts are only able to grow above minimal water activity of 0.6, the honeys under investigation should be regarded as safe with respect to fermentation.…”
Section: Resultssupporting
confidence: 88%
“…For all honeys (N = 150) investigated in this study the values of the parameters were: a = 0.23 ± 0.02, b = 0.019 ± 0.001 and r was found to be 0.843. The correlation between a w and the water content of the investigated honeys was compared with those found by other researchers (Beckh, Wessel, & Lü llmann, 2004;Cavia et al, 2004;Chirife et al, 2006;Ruegg & Blanc, 1981;Salamanca et al, 2001) who determined water content in honey by measurement of refractive index. All of them obtained a linear dependence of a w on water content and proposed Eq.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The water content values determined in this study agree with the values reported for Chinese honeys (19.8 -29.0%) (Junzheng & Changying, 1998), but are higher than those reported for honeys from Australia (15.8 -18.0%) (Sopade et al, 2002), from Poland (15.4 -18%) (Juszczak & Fortuna, 2006), from Mexico (Table 1). The water activity of honey was due to its sugar composition and concentration (Gleiter, Horn, & Isengard, 2006), but also to the water content (Mora-Escobedo et al, 2006;Chirife et al, 2006;Gleiter et al, 2006;Cavia, Fernandez-Muino, Huidobro, & Sancho, 2004). The results of this work agree with these as the water activity varied linearly (Equation 1) with the water content (Figure 1), similarly to observed by Cavia et al, 2004.…”
Section: Resultssupporting
confidence: 84%
“…Chirife et al (2006) theoretically showed that, for small moisture content intervals of honey, a linear relationship between water activity and % moisture should be expected. Several literature studies using floral honey from different origins have reported (Cavia et al 2004;Chirife et al 2006;Estupiñan et al 1998) such linear regression relationship; however, slope and intercepts were not identical but similar, as will be observed later in this paper. Coefficients of determination also varied from one study to another.…”
Section: Introductionsupporting
confidence: 47%